Plasma Fibrinogen and Echocardiography as Diagnostic Tool for Left Ventricular Hypertrophy among CKD Patients - Huma Hussain, Muniza Saeed, Hifza Noor Lodhi, Shagufta Khaliq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Left ventricular hypertrophy is the most common cardiac event associated with chronic kidney disease. Aim: To detect LVH by echocardiography among CKD patients and co-relationship between plasma fibrinogen and left ventricular mass index. Study Design: Observational study. Methodology: It was an observational study with total of 62 CKD patients enrolled through convenience sampling. Patient’s age ranged from 35-65 years. Almost 3ml of blood was taken for measuring serum creatinine and fibrinogen. Blood was centrifuged for plasma separation than stored at -20°C. ECG findings were confirmed by echo in all enrolled patients. Data was evaluated by SPSS v.24. The results were presented as counts (percentage), means and standard deviation as appropriate. Spearman correlation was applied to check the correlation of variables. Results: Echo confirmed that LVH was found in 41 (66.1%) patients with systolic dysfunction. There was a high level of plasma fibrinogen in 73% of enrolled participants. No correlation between plasma fibrinogen and LVMI was found. Practical Implication: Current project helped health providers to diagnose cardiac event at an early stage among patients of kidney failure on echo findings along-with plasma fibrinogen levels thus the adverse outcomes could be prevented or delayed. Conclusion: It was concluded that echocardiography is a helpful diagnostic tool as it confirms ECG abnormalities seen in hospitalized CKD patients. All CKD patients should have their echocardiography done. Plasma fibrinogen levels were raised with declining renal function. Thus combination of both echo and fibrinogen levels among CKD are handful investigations for LVH. Keywords: Echocardiography, Chronic Kidney Disease, Left Ventricular Hypertrophy and Plasma Fibrinogen.